2010
DOI: 10.1099/mic.0.035840-0
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic lack of glucose utilization in Streptomyces clavuligerus is due to inefficient expression of the glucose permease gene

Abstract: Streptomyces clavuligerus ATCC 27064 is unable to use glucose but has genes for a glucose permease (glcP) and a glucose kinase (glkA). Transformation of S. clavuligerus 27064 with the Streptomyces coelicolor glcP1 gene with its own promoter results in a strain able to grow on glucose. The glcP gene of S. clavuligerus encodes a 475 amino acid glucose permease with 12 transmembrane segments. GlcP is a functional protein when expressed from the S. coelicolor glcP1 promoter and complements two different glucose tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…This gene is recognized as a key factor that may contribute to "glucose repression" of nonpreferred sugars (1,6,44). However, defective and suspended D-glucose consumption had previously been observed in E. coli, B. subtilis, and S. clavuligerus when genes responsible for glucose transport were inactivated or were expressed at low levels (13,34,35). Thus, it was possible that glcG would not be an ideal gene target for engineering to relieve "glucose repression."…”
Section: Discussionmentioning
confidence: 99%
“…This gene is recognized as a key factor that may contribute to "glucose repression" of nonpreferred sugars (1,6,44). However, defective and suspended D-glucose consumption had previously been observed in E. coli, B. subtilis, and S. clavuligerus when genes responsible for glucose transport were inactivated or were expressed at low levels (13,34,35). Thus, it was possible that glcG would not be an ideal gene target for engineering to relieve "glucose repression."…”
Section: Discussionmentioning
confidence: 99%
“…A 550-bp fragment of S. coelicolor M145 that contains the rpoZ gene with its promoter and terminator sequences was amplified with primers RPOZ-Cu1 (5Ј-GGGCCTCTAGATAAGTCAGCGCA) and RPOZ-PD (5Ј-ACGAGCTGGATCCGCAGGCTCA), which had been modified with XbaI and BamHI restriction sites, respectively. The PCR product was cloned into pRA (36), an integrative conjugative plasmid. In order to introduce the complementation plasmid in the apramycin-resistant ⌬rpoZ mutant strain, a 1.4-kb fragment containing the Tn5/Neo resistance gene was cloned in the EcoRV site of pRA.…”
Section: Methodsmentioning
confidence: 99%
“…1a). Moreover, this position is not included in the PhoP core operator (28), so it should not be involved in PhoP binding. Our results with the M1 mutant confirmed that the AfsR and PhoP binding sequences start at positions displaced in 1 nucleotide.…”
Section: Analysis Of the Phop And Afsr Binding Sequences In The S Comentioning
confidence: 99%